Annual report: 2017 - Prince Mohammad Bin Fahd University (Al Khobar: Prince Mohammad Bin Fahd University, 2017)
Prince Mohammad Bin Fahd University annual report for 2017.
2
Keywords: Education, Higher -- Saudi Arabia; Private universities and colleges -- Saudi Arabia; Universities and colleges -- Saudi Arabia